RESPONSE OF YIELD AND CHEMICAL COMPOSITION OF BLACK CUMIN TO DIFFERENT FERTILIZER IN SULAIMANI REGION - M., Shnrwe B.; Ahmed, R. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Two field experiment were conducted to evaluate the effect of different fertilizer on seed yield and oil content of two Black cumin species (Nigella sativa and Nigella arvensis), the first experiment was conducted at Qlyasan Agricultural Research Qlyasan Agricultural Research Station, College of Agricultural Engineering Sciences, University of Sulaimani, and the second experiment was conducted at Kanipanka Research Station, Sulaimani Agricultural Directorate, Ministry of Agriculture and Water Recourses during the autumn season of 2020-2021. The field experiment was laid out according to factorial Completely Randomized Block Design (CRBD), with three replications. The results demonstrated that Nigella sativa gave maximum values for seed yield, fixed oil %, and essential oil% while Nigella arvensis produced maximum values for chemical constituents Thymoquinone and Nigellone at both location and their averages. The %2 organic matter produced maximum for all studied characters. The variation amount of seed yield, oil %, Essential oil % and chemical Constituents Thymoquinone and Nigellone were noticed due to the interaction treatment of N. Arvensis and %2 organic matters, at both locations and their average. Kanipanka location was significantly predominated Qlyasan location in seed yield, essential oil %, Nigellone and Thymoquinone.